2012
DOI: 10.1515/bmc-2012-0019
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of cell invasion – the trophoblast model

Abstract: Trophoblast implantation and placentation allow the survival of the young embryo and its normal development inside the uterus. In order for these processes to function properly, the trophoblast has to undergo a series of characteristic changes that lead to its adhesion and invasion of the uterus. This is achieved, among other mechanisms, by inactivation of specific tumor suppressor genes, commonly by methylation of their promoters. Cell adhesion and tissue invasion are also characteristics of malignant tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…SFRP5 inactivates the Wnt/β-catenin signalling pathway by decreasing phosphorylated GSK3β and non-phosphorylated β-catenin (active β-catenin) and subsequent T-cell transcription factor 4 (TCF4)/lymphoid enhancer-binding factor 1 (LEF1)-mediated gene expression in cancer cells and pluripotent stem cells [56][57][58]. Since the invasive behaviour of trophoblasts in early placentation is similar to that of tumour cells, we hypothesised that SFPR5 might have a similar effect on their function [59,60]. Using SFRP5 recombinant protein, we demonstrated that SFRP5 inhibited trophoblast migration and invasion by increasing GSK3β and decreasing β-catenin levels in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFRP5 inactivates the Wnt/β-catenin signalling pathway by decreasing phosphorylated GSK3β and non-phosphorylated β-catenin (active β-catenin) and subsequent T-cell transcription factor 4 (TCF4)/lymphoid enhancer-binding factor 1 (LEF1)-mediated gene expression in cancer cells and pluripotent stem cells [56][57][58]. Since the invasive behaviour of trophoblasts in early placentation is similar to that of tumour cells, we hypothesised that SFPR5 might have a similar effect on their function [59,60]. Using SFRP5 recombinant protein, we demonstrated that SFRP5 inhibited trophoblast migration and invasion by increasing GSK3β and decreasing β-catenin levels in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The cells (5 × 10 3 ) were seeded in 96-well plates and incubated at 37°C for 12 h. Serum-free medium was subsequently added, and the cells were incubated in a 5% CO 2 incubator at 37°C. The medium was replaced with fresh medium containing different concentrations of lithium chloride (LiCl, canonical Wnt agonist) (1, 10, 20, 50, and 500 μM, as well as 1, 2, 5, 10, 20, 30, 40, and 50 mM) and recombinant Dickkopf-related protein 1 (Dkk-1, canonical Wnt inhibitor) (1,2,5,10,20,50,60,80, and 100 ng/mL); these concentrations were selected based on previous studies [29][30][31][32][33][34][35]. After incubation for 12 h at 37°C, 10 μL CCK8 reagent was added to each well, and the plate was incubated for 1 h at 37°C.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…The most important difference between placentation and tumorigenesis is that the invasion of trophoblasts is spatially and temporally regulated; therefore, the invasion is neither too shallow, as it is in PE and IUGR, nor too deep, as it is in placenta accreta or percreta. Previous studies emphasized the similarities between placental and tumor tissues and research mostly progressed in the direction of using the knowledge about trophoblast behavior to better understand tumor behavior [33,34]. In recent years, there have been more and more studies where a certain molecule found to be important for the behavior or targeting of tumor cells has subsequently been associated with the functioning of trophoblasts and gestational diseases [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%